Measures of body fatness and height across the adult lifecourse and prostate cancer risk and mortality in the pooling project of prospective studies of diet and cancer - Genkinger, JM; Wu, K; Wang, M; Travis, R; Key, T; Et al. (Oxford University Press, 2020)
Background: Advanced prostate cancer etiology is poorly understood. Few studies have examined associations of anthropometric factors (e.g. early adulthood obesity) with advanced prostate cancer risk. Patients and methods: We carried out pooled analyses to examine associations between body fatness, height, and prostate cancer risk. Among 830 772 men, 51 734 incident prostate cancer cases were identified, including 4762 advanced (T4/N1/M1 or prostate cancer deaths) cases, 2915 advanced restricted (same as advanced, but excluding localized cancers that resulted in death) cases, 9489 high-grade cases, and 3027 prostate cancer deaths. Cox proportional hazards models were used to calculate study-specific hazard ratios (HR) and 95% confidence intervals (CI); results were pooled using random effects models. Results: No statistically significant associations were observed for body mass index (BMI) in early adulthood for advanced, advanced restricted, and high-grade prostate cancer, and prostate cancer mortality. Positive associations were shown for BMI at baseline with advanced prostate cancer (HR = 1.30, 95% CI = 0.95–1.78) and prostate cancer mortality (HR = 1.52, 95% CI = 1.12–2.07) comparing BMI ≥35.0 kg/m2 with 21–22.9 kg/m2. When considering early adulthood and baseline BMI together, a 27% higher prostate cancer mortality risk (95% CI = 9% to 49%) was observed for men with BMI <25.0 kg/m2 in early adulthood and BMI ≥30.0 kg/m2 at baseline compared with BMI <25.0 kg/m2 in early adulthood and BMI <30.0 kg/m2 at baseline. Baseline waist circumference, comparing ≥110 cm with <90 cm, and waist-to-hip ratio, comparing ≥1.00 with <0.90, were associated with significant 14%–16% increases in high-grade prostate cancer risk and suggestive or significant 20%–39% increases in prostate cancer mortality risk. Height was associated with suggestive or significant 33%–56% risks of advanced or advanced restricted prostate cancer and prostate cancer mortality, comparing ≥1.90 m with <1.65 m. Conclusion: Our findings suggest that height and total and central adiposity in mid-to-later adulthood, but not early adulthood adiposity, are associated with risk of advanced forms of prostate cancer. Thus, maintenance of healthy weight may help prevent advanced prostate cancer.